Neural mechanism in anterior prefrontal cortex for inhibition of prolonged set interference - Konishi, Seiki (National Academy of Sciences, 2005)
Once one cognitive set dominates our behavior, it continues to influence subsequent behavior for a while even after a task to be performed is changed to another. Despite abundant knowledge of the inhibitory mechanisms that are recruited at the first trial after the change (the first inhibition trial), little is known about the inhibition of prolonged proactive interference from a previous set that lingers for several trials after the first inhibition trial. The present functional MRI study explored the neural mechanisms for inhibition of a previous set that were recruited after the first inhibition trial. A modified Wisconsin Card Sorting Test was used where “dual-match stimuli” were intermittently presented and allowed subjects to perform correctly based on previously appropriate, now inappropriate, responses. In response to the dual-match stimulus at “release” trials presented after the first inhibition trials, the subjects were transiently exempted from inhibiting the prolonged previous set. As expected from the exempted inhibitory demands, significant reaction time decrease was revealed in the release trials. Consistent with the behavioral results, transient signal decrease time-locked to the release trials was revealed in the left anterior part of the superior frontal sulcus. Moreover, the anterior prefrontal region was not sensitive to the task change, which exhibited a marked contrast to the left posterior inferior prefrontal region that showed significant signal changes in both events. These results revealed multiple inhibitory mechanisms in the lateral prefrontal cortex that are recruited in different temporal contexts of the interference from a previous cognitive set.